Study on the genus Morulina (Collembola: Neanuridae) with description of a new species from Northwest China - Palacios-Vargas, José G.; Gao, Yan (Zootaxa, 2013)
A new species of Morulina from China is described and illustrated. It is close to M. orientis Tanaka from Japan and M. himalayana Cassagnau from Nepal. There are 12 tubercles on the head of all three species, but they can be separated by a number of chaetotaxic characters. A key for identification of all the species in the genus is given.